Preliminary assessment of Salvadora persica whitening effects on extracted stained teeth - Nadia Halib; Nabilah Bt Nuairy; Haslinda Ramli; Ishak Ahmad; Norinsan Kamil Othman; Salihatun Md Salleh; Saiful Bahari Bakarudin (Open Science Publishers LLP Inc., 2024)
Indexed by Scopus